Effect of cashless policy on agricultural activities of arable crop farmers in Egbeda, Oyo State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
A cashless policy decreases the bulk of physical cash that individuals/corporate bodies carry for business transactions on a daily basis. This study analysed the effects of the cashless policy on the agricultural activities of arable crop farmers in Egbeda Local Government, Oyo State. A descriptive research design was used for this study. The data source was primary, and valid responses were used through the interview schedule. A multi-stage sampling procedure was used to select 120 respondents.  Data were analysed using frequency, percentage, mean, and Pearson’s Product-Moment Correlation (PPMC) at p=0.05. The results revealed that respondents had an average age of 52 years, 6 persons per household, 21.9 years of farming experience, and 2.8 hectares of farm size. The cashless policy positively impacted areas of transparency of financial transactions (x̄=3.78), convenience of financial transactions (x̄=3.77), and effective management of financial records (x̄=3.74). However, on a negative note, it aided difficulties in accessing funds promptly due to technical issues (x̄=3.68). Respondents were able to cope with cashless policy difficulties by opening mobile banking accounts to make transactions (91.7%) and maintaining detailed records of financial transactions (85.0%). There was no significant relationship between engagement in the utilisation of the cashless policy and arable crop farmers’ production in the study area. The study concluded that the cashless policy had brought about positive and negative effects on the finances of arable farmers. The study recommends more awareness, increased mobile/internet network coverage, and availability of more cash points to support arable crop farmers to adapt effectively to the cashless policy.
Keywords: Arable crop; Cashless policy; Farming; Financial transaction; Mobile banking